2015
DOI: 10.1007/s13199-015-0325-3
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal Fungi (AMF) increase the content of biomolecules in leaves of Inga vera Willd. seedlings

Abstract: Ingazeira (Inga vera Willd.), a plant native to Brazil is commonly used by Brazilians for its medicinal properties and the value of its wood. Various plants with therapeutic properties and economic importance benefit from mycorrhizal inoculation, which produces larger quantities of therapeutic compounds. However, the effects of mycorrhizal inoculation on ingazeira have not yet been studied. The objective of this paper is to evaluate the effectiveness of arbuscular mycorrhizal fungi (AMF) on the growth of seedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 33 publications
0
16
2
Order By: Relevance
“…Other studies with legumes had also reported such benefit with the inoculated AMF favoring the increase of species and, in contrast with our study, producing more mycorrhizal structures than the control treatment [37]. However, in seedlings of Inga vera , legume occurring in the caatinga, mycorrhized with A. longula , G. albida , and C. etunicatum [38] as well as in inoculated L. ferrea established in the field [27], the inoculation with AMF did not result in difference in the root diameter in relation to the non-inoculated control. This benefit may be associated with the presence of arbuscules in the inoculated roots since such structure favors the exchange of nutrients in the roots [39], resulting in greater development.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…Other studies with legumes had also reported such benefit with the inoculated AMF favoring the increase of species and, in contrast with our study, producing more mycorrhizal structures than the control treatment [37]. However, in seedlings of Inga vera , legume occurring in the caatinga, mycorrhized with A. longula , G. albida , and C. etunicatum [38] as well as in inoculated L. ferrea established in the field [27], the inoculation with AMF did not result in difference in the root diameter in relation to the non-inoculated control. This benefit may be associated with the presence of arbuscules in the inoculated roots since such structure favors the exchange of nutrients in the roots [39], resulting in greater development.…”
Section: Discussioncontrasting
confidence: 74%
“…Similar results had been reported regarding leaves of Pogostemon patchouli Pellet, inoculated with native fungi presenting increase in the concentration of flavonoids and tannins [11]; in roots of Glycyrrhiza glabra L. a legume species, mycorrhization also increased the concentration of these compounds [37]; the shoots of mycorrhized Viola tricolor L. presented an increase in the concentration of flavonoid and rutin in relation to the non-inoculated control [41]. Seedlings of native legume species of caatinga biome also presented an increase in the concentration and foliar content of flavonoids and tannins [38, 42]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in the production of secondary compounds in plants may also have an influence on the presence of microorganisms, such as arbuscular mycorrhizal fungi (AMF) (Mandal et al 2015). These fungi are obligate biotrophs, belonging to the phylum Glomeromycota (Schübler et al 2001), having a symbiotic association with most of the terrestrial plant species, forming the mycorrhizal association (Smith and Read 2008), which influences the nutrition, physiology, and biochemistry of plants (Moreira and Siqueira 2002) therefore being able to increase the production of secondary compounds (Lima et al 2015;Oliveira et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Tree legumes occurring in the Brazilian semi-arid region have recorded higher production of phenolic compounds (Pedone-Bonfim et al 2013, Silva et al 2014a, 2014bLima et al 2015;Oliveira et al 2015); however, for M. tenuiflora, ''jurema preta'' (Maia 2004), legume that forms mycorrhiza (Gattai et al 2011), no records have been found regarding the influence of these fungi on the increase of the production of foliar phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%